Relation between aerodynamic force and flight posture in the flight phase training of ski jumping using wind tunnel - Akashi, K.; Yamanobe, K.; Shirasaki, K.; lshige, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The wind environment imitating the flight phase of ski jumping is duplicated in the wind tunnel laboratory and ski jumpers (20.7*7.1yrs) trained there for flight phase. The purpose of this study was to get the suggestion about the flight posture to extend a flight distance to analyze aerodynamic force and flight posture at the training. As the result, the jumper having high L/D was small forward leading angle, attack angle of attack, attack angle of lower limb and bending angle of shoulder (p< .01-05). the jumper having large SR was large attack angle of ski and small forward leading angle (p < .01).